2005
DOI: 10.1634/stemcells.2004-0107
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Intervertebral Disc–Like Cells From Adult Mesenchymal Stem Cells

Abstract: The potential of adult mesenchymal stem cells (MSCs) to differentiate towards cartilage, bone, adipose tissue, or muscle is well established. However, the capacity of MSCs to differentiate towards intervertebral disc (IVD)-like cells is unknown. The aim of this study was to compare the molecular phenotype of human IVD cells and articular chondrocytes and to analyze whether mesenchymal stem cells can differentiate towards both cell types after transforming growth factor β (TGFβ)-mediated induction in vitro.Bone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
173
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 232 publications
(178 citation statements)
references
References 36 publications
4
173
0
1
Order By: Relevance
“…Thus the potential of allogenic stem cells is worthy of further investigations using longer time points and larger animal models. [75]. Microarray analyses of the gene expression profiles were more consistent with annulus fibrosus cells of the IVD than a chondrocyte profile [75].…”
Section: Potential Of Allogenic Mscs In Ivd Regenerationmentioning
confidence: 97%
See 1 more Smart Citation
“…Thus the potential of allogenic stem cells is worthy of further investigations using longer time points and larger animal models. [75]. Microarray analyses of the gene expression profiles were more consistent with annulus fibrosus cells of the IVD than a chondrocyte profile [75].…”
Section: Potential Of Allogenic Mscs In Ivd Regenerationmentioning
confidence: 97%
“…[75]. Microarray analyses of the gene expression profiles were more consistent with annulus fibrosus cells of the IVD than a chondrocyte profile [75].…”
Section: Potential Of Allogenic Mscs In Ivd Regenerationmentioning
confidence: 97%
“…These cells require cell-to-cell contact on three-dimensional spheres and growth factors such as TGF-b1 for development into NP-like cells [73,88]. After differentiation, these cells can be placed on a gel scaffold or directly injected into the disc [73,88].…”
Section: Stem Cell Therapiesmentioning
confidence: 99%
“…These cells require cell-to-cell contact on three-dimensional spheres and growth factors such as TGF-b1 for development into NP-like cells [73,88]. After differentiation, these cells can be placed on a gel scaffold or directly injected into the disc [73,88]. Use of bone marrowderived mesenchymal stem cells has demonstrated the ability to slow degeneration by preserving disc health as evaluated by MRI, histology, immunohistochemistry, and gene expression [44,[78][79][80].…”
Section: Stem Cell Therapiesmentioning
confidence: 99%
“…He showed that the cells proliferate but more proteoglycan was released into the culture medium and did not stay in the implant. Even stem cells could be a source of cells for tissue engineering, as they may differentiate into cells with an IVD-like phenotype as proven with a DNA copy of the mRNA (cDNA) [22].…”
Section: Introductionmentioning
confidence: 99%